Obtaining interspecific hybrids, and molecular analysis by microsatellite markers in grapevine - Schuck, Mariane Ruzza; Biasi, Luiz Antonio; Mariano, Ada Michele; Lipski, Bernardo; Riaz, Summaira; Walker, Michael Andrew (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the potential of interspecific hybridization of Vitis labruscana and Muscadinia rotundifolia by using artificial cross‑pollinations. Microsatellite markers were used to confirm interspecific hybridizations and the identity of the parental genotypes. In crosses in which M. rotundifolia was used as the female parent, no true hybrids were obtained. In the reciprocal crosses, 114 seedlings were identified as true V. labruscana x M. rotundifolia hybrids. Self‑pollination occurred in direct and in reciprocal crosses. The crossings between 'Bordo' x 'Carlos', 'Magnolia', 'Regale' and 'Roanoke', and between 'Isabel' x 'Bountiful', 'Carlos', 'Magnolia', 'Regale' and 'Roanoke' were confirmed. The 15 markers evaluated showed that two M. rotundifolia parental genotypes had the same fingerprint profile, indicating a likely planting error. The success of hybridization depends mainly on the species and on the cultivar used as the female parent. Microsatellite markers are efficient to confirm the paternity of interspecific F1 hybrids and to determine the correct identity of M. rotundifolia cultivars.